New issues for dual-purpose breeding for chicken small producers - Badi, B.; Leroy, G.; Olori, V.E.; Dessie, Tadelle (2019)
With the world population projected to reach 8.5 billion people in 2030, more poultry meat and eggs will be needed from chickens reared in a broad range of environments and production systems. In developing countries, a large part of the poultry production rely on backyard systems raising dual- purpose indigenous animals. Value chain approaches are interesting tools to investigate the future of dual-purpose chicken production in developing countries, especially in relation to market and demand-led drivers. Other factors has yet to be considered in parallel, considering inclusiveness, especially for women, but also the potential impact of changing environment on the production systems.